The Use of Partial Least Square for Analysis of the Relationship of Family Support on Learning Outcomes and Achievements Through Learning Motivation - Septian Cahya Azhari; Ely Satiyasih Rosali; Muhammad Adlan Faishal; Nita Nurmala Dewi; Lutfiah -; Riska Setiawatil Huda; Nina Asih Rahayu; Tasya Meita (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2022)
Abstract:  This study aims to analyze the relationship of family support to learning outcomes and learning achievement through learning motivation so that parents can increase their support for children in the effort to increase their learning motivation. This study uses a quantitative approach with partial least squares (SEM-PLS) analysis. The results showed that the score of the original sample of family support to learning motivation was 0.655, the score of learning motivation to learning outcomes was 0.605, and the score of learning motivation to learning achievement was 0.487. Thus, there is a positive relationship between family support and learning motivation, learning motivation and learning outcomes, and learning motivation and learning achievement. Therefore, to improve learning outcomes, learning achievement and learning motivation of children, parents must provide optimal support in the learning process to improve children's learning motivation.